2017
DOI: 10.31235/osf.io/qa764
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Pragmatic Play? Some Possible Functions of English Emoticons and Japanese Kaomoji in Computer-Mediated Discourse

Abstract: This study compares emoticon usage in English with thetext-based Japanese version, kaomoji ("face-marks"). We analyze a corpus of CMD drawn from English andJapanese sources at the micro-level using an approach modeled on Conversation Analysis. Japanese kaomoji were chosen because they are an understudied phenomenon in the CMD research and because they vary quite dramatically from English emoticons, in both their construction and in their variety (Katsuno & Yano, 2002; Nishimura, 2003). Overall, we foun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0
6

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(31 citation statements)
references
References 7 publications
0
25
0
6
Order By: Relevance
“…Miller et al's (2016) survey of users based in the USA showed that the 304 recruited participants only agreed on the meaning of emoji in 25% of cases. Researchers have also shown that there are differences in how people from different backgrounds use graphicons, with age, gender, levels of experience in using text-based communication, and of course cultural background all being said to impact on how people use them (Alshenqeeti, 2016;Baron, 2004;Lo, 2008;Markman and Oshima, 2007;Nishimura, 2015;Sampietro, 2016a).…”
Section: Introductionmentioning
confidence: 99%
“…Miller et al's (2016) survey of users based in the USA showed that the 304 recruited participants only agreed on the meaning of emoji in 25% of cases. Researchers have also shown that there are differences in how people from different backgrounds use graphicons, with age, gender, levels of experience in using text-based communication, and of course cultural background all being said to impact on how people use them (Alshenqeeti, 2016;Baron, 2004;Lo, 2008;Markman and Oshima, 2007;Nishimura, 2015;Sampietro, 2016a).…”
Section: Introductionmentioning
confidence: 99%
“…In early research (Walther & D'Addario, ) it was suggested that emoticons could function in a similar way to fixed expressions, such as “How do you do?” (Malinowski, 1923/); rather than carrying any specific meaning, they performed a social function. Emoticons have also been compared with punctuation, either serving to enhance it (Garrison, Remley, Thomas, & Wierszewski, ), or actually functioning as punctuation (Markman & Oshima, ). This latter suggestion may partly explain why, according to Ip (), emoticons are more effective at increasing valence ratings in the absence of standard punctuation (Ip, ).…”
mentioning
confidence: 99%
“…This extract demonstrates how users have found ways of approximating facial expressions to make sure their stance is understood (Markman & Oshima, 2007). We see both Isla and Joe making use of smilies, with Isla using a face with its tongue sticking out at the end of line 3, and Joe using a “sad face” smiley at the start of his turn.…”
Section: Ca and Online Interactionmentioning
confidence: 99%